2020
DOI: 10.1128/aac.00884-20
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Small-Molecule Inhibitors Targeting Porphyromonas gingivalis Interspecies Adherence and Determination of Their In Vitro and In Vivo Efficacies

Abstract: P. gingivalis is one of the primary causative agents of periodontal disease and initially colonizes the oral cavity by adhering to commensal streptococci. Adherence requires the interaction of a minor fimbrial protein (Mfa1) of P. gingivalis with streptococcal antigen I/II (AgI/II). Our previous work identified an AgI/II peptide that potently inhibited adherence and significantly reduced P. gingivalis virulence in vivo, suggesting that this interaction represents a potential target for drug discovery. To devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Effective neutrophil responses are important both to maintain immunity at densely populated gingival surfaces and for clearance of microbes that gain systemic access. P. gingivalis and S. gordonii are synergistically pathogenic both in murine models of periodontal disease ( 15 , 22 ) and in abscesses ( 13 , 31 ). In the current study, we found that P. gingivalis could enhance the survival of S. gordonii in a murine abscess model, although this synergy was not strictly dependent on P. gingivalis -mediated disruption of neutrophil functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective neutrophil responses are important both to maintain immunity at densely populated gingival surfaces and for clearance of microbes that gain systemic access. P. gingivalis and S. gordonii are synergistically pathogenic both in murine models of periodontal disease ( 15 , 22 ) and in abscesses ( 13 , 31 ). In the current study, we found that P. gingivalis could enhance the survival of S. gordonii in a murine abscess model, although this synergy was not strictly dependent on P. gingivalis -mediated disruption of neutrophil functions.…”
Section: Discussionmentioning
confidence: 99%
“…Mitis group streptococci such as S. gordonii are abundant early colonizers of newly erupted or cleaned tooth surfaces and are a major component of developing supragingival and subgingival biofilms ( 19 ). S. gordonii can provide an attachment substratum for partner species through receptor polysaccharide (RPS) and surface protein adhesins ( 20 , 21 ), and can act as an accessory pathogen for P. gingivalis to increase community pathogenicity, or nososymbiocity, in periodontal disease ( 15 , 22 ). However, this composite outcome belies a more nuanced and multidimensional relationship between the two organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Roky identified 3 small molecules, namely N7, N17 and V8 from high-throughput screening of ZINC library, that inhibited P. gingivalis adherence to streptococci and reduced its virulence in vivo . In addition, compound N17 and V8 showed low cytotoxic activity in both human and marine cells ( Roky et al., 2020 ). Another synthetic compound PCP-III-201, firstly designed as an inhibitor that mimics the natural peptide substrate recognized by Mfa, showed marked inhibition on the adherence of P. gingivalis to streptococci by interfering Mfa and antigenI/II interaction, and thus disrupted the formation of mixed biofilms ( Tan et al., 2018 ).…”
Section: Small Molecules That Inhibit Keystone Bacteria Associated Wi...mentioning
confidence: 99%
“…Peptides mimicking this region have been shown to block the SspB-Mfa1 interaction and inhibit P. gingivalis virulence within a murine model for periodontitis (Daep et al, 2011). Furthermore, small molecule inhibitors were recently identified that similarly block the SspB-Mfa1 interaction and attenuate the ability of P. gingivalis to cause periodontitis in vivo (Roky et al, 2020). S. gordonii SspA and SspB, S. intermedius Pas, and S. mutans SpaP have also all been shown to contribute to aggregation with Actinomyces naeslundii, another organism associated with periodontitis (Jakubovics et al, 2005b).…”
Section: Niche Specific Interactions Oral Cavitymentioning
confidence: 99%
“…As mentioned, proof-ofconcept has been established with use of a peptide to block the interaction of S. gordonii AgI/II with P. gingivalis Mfa1, resulting in reduced alveolar bone resorption in a murine model of periodontitis (Daep et al, 2011). More recently, this peptide has been incorporated into polymeric nanoparticles to improve peptide dosage and persistence within the oral cavity (Mahmoud et al, 2018), while small molecule inhibitors of the AgI/II-MfaI engagement have also been found to effectively reduce P. gingivalis virulence (Roky et al, 2020). Protective effects have also been shown for a peptide (p1025) that blocks S. mutans AgI/II adhesion to SAG.…”
Section: Agi/ii Proteins As Therapeutic Targetsmentioning
confidence: 99%